2017
DOI: 10.1002/jso.24565
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size and invasiveness matters for partial nephrectomy: External validation and modification of the arterial based complexity score

Abstract: The ABC score correlates well with surgical parameters. Expanding the score by tumor diameter gives the ABCD system. It has similar predictive effectiveness to the well-established RENAL score, but features simplicity by only assessing invasiveness and tumor size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Except for one prospective randomized trial [71], all the studies were retrospective. All the studies were found to be of intermediate quality, except for one of high quality [59] ( Table 1). The majority of the studies assessed the predictive role of the RENAL and PADUA scores, mostly regarding complications after NSS ( Supplementary Fig.…”
Section: 2mentioning
confidence: 99%
See 4 more Smart Citations
“…Except for one prospective randomized trial [71], all the studies were retrospective. All the studies were found to be of intermediate quality, except for one of high quality [59] ( Table 1). The majority of the studies assessed the predictive role of the RENAL and PADUA scores, mostly regarding complications after NSS ( Supplementary Fig.…”
Section: 2mentioning
confidence: 99%
“…A cumulative analysis of three available studies [59,71,72] showed RENAL as an independent predictor of on-clamp resection (OR: 1.55; 95% CI: 1.23, 1.95; p < 0.001). Each of the PADUA, ABC [59], and MAP [72] scores was assessed in only one study and associated with on-clamp technique (all p < 0.001; Table 2 and the Supplementary material).…”
Section: The Supplementary Material)mentioning
confidence: 99%
See 3 more Smart Citations